Pengembangan Sistem Informasi dan Pemesanan Co-Working Space berbasis Web (Studi Kasus EZO Space Malang) - Widya Amala Sholikhah; Fajar Pradana; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The rapid development of co-working spaces in Indonesia according to the current list of Indonesian Co-Working Space Association (ACI), this also effects the competition in the co-working space business. As one of the co-working spaces in Malang, EZO Space currently still has problems in its business process. The room reservation process, membership registration, partnership application and room availability information system are still manual, clients must send a message via Whatsapp or comes to the place directly. Managing order data, payment data and membership data also still uses Microsoft Excel. One of the ways to achieve their successfull business is by providing system information reservation and make new innovation which name as event starter, to bring together creative workers in events they have initiated themselves. Therefore, the development of Web-Based Co-working Space Information and Booking System which is developed using programming language PHP with Laravel Framework, JavaScript, HTML5, CSS, and MySql database. The system was developed using waterfall method, limited to testing only. The system is tested using white-box testing for 3 units and black-box testing with 73 test cases which get 100% valid results, and usability testing using the System Usability Scale (SUS) method which gets a value of 75.6.